2014
DOI: 10.1186/1477-7819-12-285
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of recurrence for resected T1aN0M0 invasive lung adenocarcinoma: a clinicopathologic study of 177 patients

Abstract: BackgroundThis study aimed at identifying risk factors of recurrence for completely resected pathologic T1aN0M0 lung adenocarcinomas.MethodsWe reviewed the records of 177 T1aN0M0 invasive adenocarcinoma patients, and re-classified achieved surgical specimens according to the new International Association for the Study of Lung Cancer, American Thoracic Society, and European Respiratory Society (IASLC/ATS/ERS) lung adenocarcinoma classification. Impact on recurrence-free survival (RFS) for age, gender, smoking h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Increased post-operative recurrence for the high-risk histology group was observed despite all patients undergoing lobectomy and node dissection [26].…”
Section: Prognosis Across All Stagesmentioning
confidence: 97%
“…Increased post-operative recurrence for the high-risk histology group was observed despite all patients undergoing lobectomy and node dissection [26].…”
Section: Prognosis Across All Stagesmentioning
confidence: 97%
“…Furthermore, it is very typical for complete resection to be accompanied by follow-up, with surveillance monitoring usually being adopted thereafter. Nevertheless, majority of patients still suffer from the reoccurring LAC [5]. Moreover, cisplatin has been shown to be essential when treating LAC, with its sensitivity to cisplatin being directly associated to the prognosis [6].…”
Section: Introductionmentioning
confidence: 99%
“…A series of studies have demonstrated that MPP is an unfavorable prognostic factor in early stage adenocarcinoma . However, other survival analyses have indicated that patients with MPP harboring EGFR mutations were reported to have better survival when they received TKI treatment compared with those who received either no treatment or conventional platinum‐based chemotherapy …”
Section: Discussionmentioning
confidence: 99%